2019
DOI: 10.1093/ofid/ofz368
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Polymyxin Resistance: End of an Era?

Abstract: Until recently, the polymyxin antibiotics were used sparingly due to dose limiting toxicities. However, the lack of therapeutic alternatives for infections caused by highly resistant Gram-negative bacteria has led to the increased use of the polymyxins. Unfortunately, the world has witnessed increased rates of polymyxin resistance in the last decade, which is likely in part due to its irrational use in human and veterinary medicine. The spread of polymyxin resistance has been aided by the dissemination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 98 publications
1
56
0
6
Order By: Relevance
“…The European Antimicrobial Resistance Surveillance Network (EARS-net) reported that 29% of carbapenem resistant K. pneumoniae were also resistant to colistin, while only 3% of carbapenem susceptible K. pneumoniae were colistin resistant (CoR). Similar results were found in a retrospective study in Dubai in which 27% of carbapenem resistant K. pneumoniae were also resistant to colistin in five of their major hospitals [32].…”
Section: Colistinsupporting
confidence: 86%
See 1 more Smart Citation
“…The European Antimicrobial Resistance Surveillance Network (EARS-net) reported that 29% of carbapenem resistant K. pneumoniae were also resistant to colistin, while only 3% of carbapenem susceptible K. pneumoniae were colistin resistant (CoR). Similar results were found in a retrospective study in Dubai in which 27% of carbapenem resistant K. pneumoniae were also resistant to colistin in five of their major hospitals [32].…”
Section: Colistinsupporting
confidence: 86%
“…A fecal study of livestock animals in Poland, Taiwan, China, and Switzerland found that colistin resistance is highest among animals. Resistance can easily spread to humans through ingestion of fecal contamination and horizontal gene transfer among host bacteria [32].…”
Section: Colistinmentioning
confidence: 99%
“…Colistin-resistant Enterobacteriaceae has become a great concern to global public health [5,6]. While several mechanisms of resistance have been elucidated, the most important one is mediated by the transferrable mcr-1 gene, which encodes the phosphoethanolamine transferase and it could be rapidly disseminated through the conjugative plasmid [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report of mcr-1 in IncI2-type plasmid pHNSHP45, a series of mcr-1-carrying plasmids have been detected, including IncHI2, 18 IncX4, 19 IncX2, 20 IncP, 21 IncII, 22 and other. 3,23 The plasmids can act as reservoirs of horizontal gene transfer. Therefore, plasmid curing is an attractive strategy to slow the spread of colistin resistance in bacteria.…”
Section: Discussionmentioning
confidence: 99%